2019
DOI: 10.1093/jmcb/mjz075
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p53 inhibitors: progress, challenges and perspectives

Abstract: p53 is the major tumor suppressor and the most frequently inactivated gene in cancer. p53 could be disabled either by mutations or by upstream negative regulators, including, but not limited to MDM2 and MDMX. p53 activity is required for the prevention as well as for the eradication of cancers. Restoration of p53 activity in mouse models leads to the suppression of established tumors of different origin. These findings provide a strong support to the anti-cancer strategy aimed for p53 reactivation. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 146 publications
1
112
0
Order By: Relevance
“…Recently, a dozen of ribosomal proteins (RPs) have been found to be dissociated from the pre-ribosomes and interact with MDM2 leading to p53 stabilization and activation upon ribosomal stress 16,17 . These findings lead to the development of several anticancer strategies by activating the tumor-suppressive function of these RPs in the wild-type p53-sustaining tumors 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a dozen of ribosomal proteins (RPs) have been found to be dissociated from the pre-ribosomes and interact with MDM2 leading to p53 stabilization and activation upon ribosomal stress 16,17 . These findings lead to the development of several anticancer strategies by activating the tumor-suppressive function of these RPs in the wild-type p53-sustaining tumors 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…PRIMA-1 MET /APR-246) and drugs designed to return functionality to WT p53 by inhibiting its upstream regulators (e.g. MDM2/X inhibitors) (Sanz et al, 2019). Here, we showed that transiently reactivating p53 in CENP-A overexpressing HeLa cells was able to significantly increase sensitivity to X-irradiation.…”
Section: Cenp-a Overexpression Drives Distinct Cell Fates Depending Omentioning
confidence: 81%
“…Consequently, inhibition of the p53-MDM2 interaction is an attractive strategy to activate p53-dependent apoptosis in a non-genotoxic manner, thus facilitating selectivity and efficiency of tumor cell elimination. [14][15][16][17] Indeed, the first-generation non-peptide small molecule MDM2 inhibitors, known as Nutlins, have been shown to activate the p53 pathway in cancer cells harboring wildtype p53 both in vitro and in vivo. Nutlins inhibit the p53-binding pocket on MDM2, resulting in the accumulation of p53 and restoration of both its transcriptional activity and ability to induce apoptosis.…”
Section: The P53 Pathway As a Therapeutic Targetmentioning
confidence: 99%